2012
DOI: 10.1016/j.jacc.2012.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and Hemodynamic Origins of Pre-Hypertension

Abstract: Objective To better understand the origins and progression of prehypertension. Background Prehypertension is a risk factor for progression to hypertension, cardiovascular disease and increased mortality. We used a cross-sectional twin study design to probe the role of heredity in likely pathophysiological events (autonomic or hemodynamic) in prehypertension. Methods 812 individuals (337 normotensive, 340 prehypertensive, 135 hypertensive) were evaluated in a sample of twin pairs, their siblings and other f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
3
23
1
2
Order By: Relevance
“…A previous study showed that elevated sympathetic tone was associated with high normal BP states, and intriguingly, it was also coupled with metabolic alterations similar to those observed in our study . Other studies have also demonstrated that decreased parasympathetic tone, along with increased sympathetic activity, underlies the pathogenesis of prehypertension . Further, our observation reinforced the notion that prehypertension is associated with subclinical target organ damage, in aspects of “vascular” and “cardiac” structure and function.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study showed that elevated sympathetic tone was associated with high normal BP states, and intriguingly, it was also coupled with metabolic alterations similar to those observed in our study . Other studies have also demonstrated that decreased parasympathetic tone, along with increased sympathetic activity, underlies the pathogenesis of prehypertension . Further, our observation reinforced the notion that prehypertension is associated with subclinical target organ damage, in aspects of “vascular” and “cardiac” structure and function.…”
Section: Discussionsupporting
confidence: 91%
“…Heterogeneity in statin responsiveness has attracted considerable attention. However, additional microarray-derived associations exist with nonlipid risk factors, such as gene expression in adipose, hepatic, and β cell tissues in obesity and diabetes107 or those relating to the origins of hypertension 108…”
Section: Genetic Contribution To Residual Riskmentioning
confidence: 99%
“…Although elevated SVR and arterial pressure are clearly relevant for cardiovascular outcomes, a derangement in pulsatile arterial hemodynamics may predict cardiovascular risk earlier, more accurately, or be associated with a different spectrum of morbidities. 25 Most previous studies have assessed pulse pressure compared with mean arterial pressure as a predictor of cardiovascular outcomes. 68 However, the determinants of pulse pressure and mean arterial pressure extend beyond large arterial properties and microvascular resistance, and depend also on the flow generated by the heart (stroke volume and cardiac output).…”
Section: Introductionmentioning
confidence: 99%